1982
DOI: 10.1017/s0022149x0003426x
|View full text |Cite
|
Sign up to set email alerts
|

Filaricidal properties of a wild herb, Andrographis paniculata

Abstract: Water decoction of the leaves of Andrographis paniculata killed in vitro the microfilaria of Dipetalonema reconditum in 40 min. Three subcutaneous injections of the extract into infected dogs at 0·06 ml per kg bodyweight reduced the number of microfilariae in blood by more than 85%. The larvae were not totally eliminated with more infections but the reduced microfilarial level persisted. No toxiceffect of the extract was observed in rabbits. The treated dogs became lethargic initially for a week, probably due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Andrographis paniculata is used as a folk medicine for reducing inflammation. Three ingredients deoxyandrographolide, Andrographolide and neoandrographolide are effective in reducing inflammation [139]. In other studies it was found that Andrographis paniculata extracted with alcohol [140,141], A. paniculata extracted with water [140] and A. paniculata extracted with chloroform [141]reduced inflammation.…”
Section: Effect On Inflammation and Fevermentioning
confidence: 99%
See 1 more Smart Citation
“…Andrographis paniculata is used as a folk medicine for reducing inflammation. Three ingredients deoxyandrographolide, Andrographolide and neoandrographolide are effective in reducing inflammation [139]. In other studies it was found that Andrographis paniculata extracted with alcohol [140,141], A. paniculata extracted with water [140] and A. paniculata extracted with chloroform [141]reduced inflammation.…”
Section: Effect On Inflammation and Fevermentioning
confidence: 99%
“…Since no toxic effects were apparent, researchers believed that the A. paniculata extract would be safe for humans. Water decoction of the leaves exhibited filaricidal activity, both in vitro and in dogs [139]. Xanthones isolated from the roots showed antiprotozoal activity against Trypanosoma brucei, Trypanosoma cruzi and Leishmania infantum [177].…”
Section: Antifilarial Antiprotozoal and Antiplasmoidal Activitymentioning
confidence: 99%
“…Andrographis lineata is an erect herb found widely in Deccan, Carnatic, Yercaud, and Nilgiri hills of South India (Gamble 1956), and the methanol and aqueous extracts established pharmacological evidence to support the folklore claim that it is used traditionally as a hepatoprotective agent (Sangameswaran et al 2008). A bitter plant, a decoction of Andrographis paniculata leaves or roots, is used as a vermifuge (Sugati et al 1999) against Dipetalonema reconditum and Brugia malayi (Dutta and Sukul 1982;Zaridah et al 2001), and the methanol and ethyl acetate extracts were tested on Callosobruchus chinensis (Bright et al 2001) and relieve itchy skin and insect bites (Burkill 1966). Cocculus hirsutus is a widely growing plant found in the plains of India in dry localities and is used medicinally by the Indian tribes for a wide range of ailments, including constipation and kidney problems (Caius 1986;Usher 1984), and the aerial parts aqueous extract showed significant diuretic activity and laxative effect in rats (Ganapaty et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Andrographis paniculata leaves or roots decoction are used as a vermifuge (Sugati et al 1999), against Brugia malayi (Zaridah et al 2001), 100% mortality obtained against the microfilaria of Dipetalonema reconditum (Dutta and Sukul 1982), the methanol and ethyl acetate extracts were tested on cowpea weevil, Callosobruchus chinensis (Bright et al 2001), and relieve itchy skin and insect bites (Burkill 1966). Cocculus hirsutus is a widely growing plant found in the plains of India and the aerial parts aqueous extract showed significant diuretic activity and laxative effect in rats (Ganapaty et al 2002).…”
Section: Introductionmentioning
confidence: 99%